1610. Epidemiology and Treatment Heterogeneity in Acinetobacter baumanii Infections. (31st December 2020) - Caffrey, Aisling; Appaneal, Haley J; Lopes, Vrishali; LaPlante, Kerry
Abstract: Background: Acinetobacter baumannii is known as a highly resistant organism causing serious infections in intensive care populations. However, the epidemiology of infections caused by Acinetobacter baumannii and approaches to treatment are not well described in a national healthcare system. Methods: Our retrospective cohort study included patients with positive Acinetobacter baumannii cultures collected from any source during hospitalizations at Veterans Affairs (VA) medical centers nationally from January 2010 to April 2019. We evaluated patient characteristics and utilized exposure mapping to identify treatment patterns, including treatment heterogeneity. Heterogeneity was defined as patterns of antibiotic treatment (drug and duration) not shared by any other patient. Results: Our study included 7, 551 admissions with positive Acinetobacter baumannii cultures. The mean age was 66.7 years (±12.1) and 97.4% were male. Most patients were admitted from other healthcare facilities (59.2%) and 20.8% were in intensive care during the admission. Most patients had their culture collected on the day after admission and the median time to culture completion was 4 days (interquartile range 3-5). Acinetobacter baumannii cultures were most commonly obtained from urine (33.6%), followed by skin and soft tissue (25.3%), lung (21.8%), blood (9.2%), and bone/joint (5.0%). The median length of hospital stay was 11 days, with inpatient mortality and 30-day mortality rates of 11.6% and 12.5%, respectively. Treatment heterogeneity was high, with 88.5% of admissions having different antibiotic treatment patterns (drug and duration), with a median time to first change of 1 day and median of 3 changes. Only 2% of the admissions were treated with polymyxins and 3.0% with colistin. Carbapenems were used in 18.9% of the admissions and extended-spectrum cephalosporins in 31.7% of the admissions. Conclusion: In VA hospitals, Acinetobacter baumannii infections are observed in both critical and non-critical patient populations, mostly among patients with healthcare exposures. Acinetobacter baumannii infections were found to have various sources of infection, mostly from urine and skin and soft tissue, and approaches to treatment were highly varied. Disclosures: Aisling Caffrey, PhD, Merck (Research Grant or Support)Pfizer (Research Grant or Support)Shionogi (Research Grant or Support) Haley J. Appaneal, PharmD, Shionogi, Inc. (Research Grant or Support) Kerry LaPlante, PharmD, Merck (Advisor or Review Panel member, Research Grant or Support)Ocean Spray Cranberries, Inc. (Research Grant or Support)Pfizer Pharmaceuticals (Research Grant or Support)Shionogi, Inc. (Research Grant or Support)